Secular Variations of Helium and Nitrogen Isotopes Related to the 2015 Volcanic Unrest of Mt. Hakone, Central Japan. (6th November 2019) - Kagoshima, T.; Sano, Y.; Takahata, N.; Lee, H.; Lan, T.; Ohba, T.
Abstract: A small hydrovolcanic eruption occurred on Mt. Hakone in central Japan on 29 June 2015, ejecting small amounts of volcanic ash and gas. We have conducted continuous surveys of He isotopes in the Owakudani geothermal area close to Mt. Komagatake, the central cone of Mt. Hakone. Long‐term (decadal‐scale) data from the Black‐egg site show generally constant 3 He/ 4 He ratios with 6.37 ± 0.06 Ra, where Ra is the atmospheric 3 He/ 4 He ratio of 1.382 × 10 ‐6, after air correction. Short‐term (monthly) data of two fumarole sites indicate a rapid increase from May through August 2015 and a gradual decrease through February 2018, whereas seismic activity began to intensify in March 2015, reached the maximum in May, and decreased faster than the decrease in He isotopes. We also measured N and Ar isotopes in fumarole samples. A δ 15 N – N2 / 36 Ar diagram shows that they are well explained by mixing of atmosphere and volcanic gas source components. Monthly variations of air‐corrected δ 15 N values shows a rapid decrease followed by a slow increase, contrary to the air‐corrected 3 He/ 4 He variations, suggesting a common mechanism of mixing between magma and crust during migration of fluids and gases. The time sequence of observed phenomena shows inflation of the volcanic edifice, maximum swarm activity, phreatic eruption, and maximum He and N isotope anomaly. Temporal variations of He and N isotopes were correlated with activation of the Owakudani geothermal system and with termination of volcanic unrest, which may provide useful information for observing and assessing geothermal activity around the world. Key Points: Secular variations of He isotopes reflected the 2015 volcanic unrest of Mt. Hakone in Japan Corrective method of N isotopes for air contamination was proposed by N2 /Ar ratios Air‐corrected N isotopes showed anticorrelation with that of He